Stressor in Public Higher Education of Romania - Enescu, George; Irina, Simionescu (Barbu) (Advances in Social Sciences Research Journal, 2016)
The global economy’s complex dynamics causes changes in various sectors of activity in all the countries worldwide and furthermore in a country like Romania, where the outstanding change of the political regime has driven to radical changes throughout society in all environments and globalization, regionalization followed the European trend. Higher education differs itself from other types of education because the activities are carries out simultaneously on two levels: teaching and scientific research, which entail a very high level of intellectual consumption for the people involved. The Romanian higher education deeply felt all these changes and sought to adapt. In this process the expression of several internal factors grew enhanced causing the employees to be stressed above a harmless level, which brought poor performance in their activity. This paper analyses to what extent the effects of this stressor are felt by teachers in public education of Romania and proposes their review and the use of the due levers so that to mitigate negative effects.